МІКРОМІЦЕТИ КОРЕНЕВОЇ ЗОНИ РОСЛИН СОЇ КУЛЬТУРНОЇ ТА ЇХНЯ ФУНКЦІОНАЛЬНА ДІЯ НА РОСЛИНИ - Копилов, Є. П.; Шаховніна, О. О.; Надкернична, О. В.; Новікова, Т. П.; Тарасов, В. В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2022)
Objective. Characterize the fungal coenosis of the root zone of soybean plants and investigate the functional effect of isolated micromycetes on plants. Methods. The mycocenosis of different spheres of the root zone of soybean plants was studied under the conditions of field experiments on sod-medium-podzolic dusty-sandy soil. Soil sampling, isolation, accounting and cultivation of fungi were carried out according to generally accepted methods. Measuring the number of micromycetes in the spacing and the rhizosphere of soybean was carried out by the Waksman’s soil dilutions method. To extract mycobiota of rhizoplane, the method of washing from the surface of soybean roots, followed by dilution and deep sowing in the digest medium was used. Endophytes were isolated from the tissues of healthy unaffected soybean roots after their surface sterilization with alcohol (96%) for 1.5 min. Cultural and morphological characteristics of fungi were studied on wort agar, Chapek's agar medium, and potato-glucose agar. Their identification was carried out according to the determinants appropriate for a specific systematic group of micromycetes. The functional effect of micromycetes on plants was evaluated using bioassays on corn seedlings. Results. The mycocenosis of sod-podzolic soil was formed by micromycetes belonging to the genera Acremonium Link, Alternaria Nees, Cladosporium Corda, Fusarium Link:Fr, Gliocladium Corda, Mortierella Coem, Mucor Mich, Penicillium Link:Fr, Rhizopus Ehrenb, Trichoderma Hers, among which micromycetes of the genus Penicillium (28.05 ± 3.13 thous CFU per 1 g of dry soil) were the most common. Under the influence of root exudates, the total number of soya bean rhizospheric soil fungi increased threefold and amounted to 212.30 ± 16.73 thous CFU per 1 g of dry soil; in the rhizosphere fungi of the genus Fusarium prevailed (152.63 ± 13.27 thous CFU per 1 g of dry soil). Mycocenosis of the rhizoplane of soybean plants was qualitatively and quantitatively depleted, as compared to the rhizosphere, and consisted mainly of representatives of the genera Fusarium (10.18 ± 3.93 thous CFU per 1 g of dry roots) and Gliocladium (6.88 ± 1.20 thous CFU per 1 g of dry roots). The endophytic mycobiota of soybean was formed by micromycetes of the genera Penicillium (44 %), Chaetomium (21 %), Fusarium (21 %), Verticillium (7 %), Phoma (7 %). Micromycetes isolated from the root zone of soybean plants differed in their functional effect on plants. The largest share of the studied fungi (61 %) are producers of growth-stimulating substances of various origin, 18 % of strains are characterized by a phytotoxic effect on plants, 21 % do not have a pronounced effect on plants. Conclusion. The fungal coenosis of the root zone of soybean was characterized, the functional effect of isolated micromycetes on plants was investigated.